Transforming waste into value: Single-step in situ synthesis of magnetic porous carbon composite adsorbents from sugarcane bagasse and iron scrap - Sirinad Mahawong; Parichart Onsri; Piyatida Thaveemas; Sulawan Kaowphong; Supinya Nijpanich; Natthanan Rattanachueskul; Supanna Techasakul; Laemthong Chuenchom; Decha Dechtrirat (Scientific Reports)
Abstract The demand for sustainability is driving research into new ways to make use of waste products. Porous adsorbents with magnetic properties are reusable and do not require a significant external energy source. They are well-suited to the task of decontaminating water on a large scale and, if benignly synthesized from waste products, they would meet the demand for sustainability. In this research, an in situ single-step synthesis is developed that generates a magnetic porous carbon composite from iron scrap and sugarcane bagasse, both of which are abundant waste products. This procedure combines the processes of carbonization, magnetization, and activation in one step. Iron scrap serves as both a magnetic precursor and a self-activating agent, so no additional chemical activators are required. The large surface area (505 m2/g) of the synthesized magnetic porous carbon composite adsorbent and its large capacity for tetracycline adsorption (687.6 mg/g) are suitable properties for the treatment of contaminated wastewater. The synthesis process is straightforward, and the use of waste materials to fabricate an adsorbent that retains its performance even after five cycles of adsorption and desorption ensures both cost-effectiveness and sustainability to support the concept of the circular economy.